Optimization of Ultrasonic Combined with Enzymatic Extraction Process of Total Alkaloids from Artemisia argyi Leaves and Its Antibacterial Activity - Yang CHEN; Ziwei LIAO; Juanjuan TAO; Dan JIANG; Daihua SUN; Zhiyuan CHEN (Shipin gongye ke-ji, 2022)
The yield of total alkaloids from Artemisia argyi leaves was used as the index, and the optimal range conditions of solid-liquid ratio, compound enzyme addition amount, enzymolysis time, enzymolysis pH, ultrasonic time, ultrasonic power, ethanol concentration and ultrasonic temperature were obtained through single factor experiments. The Plackett-Burman method was employed to screen out the factors that had significant effects on the yield of total alkaloids from Artemisia argyi leaves. The Box-Behnken method was used to optimize the extraction process to obtain the optimun extraction conditions. Finally, the inhibitory effect and the minimum inhibitory concentration of the total alkaloid extract of Artemisia argyi leaves against Escherichia coli and Staphylococcus aureus were investigated. The results showed that the important factors affecting the yield of total alkaloids from Artemisia argyi leaves were ultrasonic time, compound enzyme addition amount and enzymolysis time. The optimum extraction conditions were as follows: Ultrasonic time 40 min, compound enzyme addition 1.60%, enzymolysis time 1.5 h, solid-liquid ratio 1:25 g/mL, enzymolysis pH6.0, ultrasonic power 160 W, ethanol concentration 80%, ultrasonic temperature 60 ℃. Under the optimized conditions, the highest yield of total alkaloids was 0.720±0.05 mg/g. The total alkaloids from Artemisia argyi leaves had antibacterial activity against Escherichia coli and Staphylococcus aureus, and their minimum inhibitory concentrations were 3.2 and 1.6 mg/mL, respectively. The actual value of the extraction process and the predicted value had a high degree of fit, which was reliable for prediction of the extraction of the total alkaloids from Artemisia argyi leaves, and the obtained total alkaloids from Artemisia argyi leaves had a certain antibacterial activity.